ARTYKUŁY WOJSKOWE AUTORAMENTU CUDZOZIEMSKIEGO WŁADYSŁAWA IV – OKOLICZNOŚCI POWSTANIA I ICH CHARAKTERYSTYKA - Łopatecki, Karol (Zeszyty Prawnicze, 2016)
THE ORIGINS AND CHARACTERISTICS OF WŁADYSŁAW IV’S MILITARY REGULATIONS FOR FOREIGN CONTINGENTS Summary Władysław IV’s military reforms are recognized as one of the most important historical, military transformations in Poland. This ruler modeled his reforms on Swedish and Western European solutions by creating a foreign military contingent. In principle, it sought to abandon the recruitment of expensive, undisciplined and often disloyal soldiers from neighboring countries. His solution was to create a contingent of the king’s subjects led by individuals knowledgeable in the conduct of modern warfare. In 1629, even before ascending to the throne, he began putting together a new type of regiments – one with domestic recruits led by professional foreign officers. At the end of 1632, Moscow attacked the Ground Duchy of Lithuania. Władysław IV, an elected king, went to the aid of the fortress, leading forces modeled on foreign military designs. Consequently, this led to the creation of the so-called “foreign contingent.” On September 6th 1633, military regulations were announced for these new type of military forces. Those rules were a faithful translation of Gustav II Adolf’s 1632 military regulations. They were originally in force in the Polish Kingdom’s armies, and from the second half of the 17th century, also in the Grand Duchy of Lithuania. During the first half of the 17th century, those regulations were not used by the contingents recruited from abroad or by reiter cavalry. Despite attempts to marginalize these regulations, they survived until the end of John III Sobieski’s reign. During this period, minor editorial changes can be noted, along with the addition and removal of minor legal directives. It was not until the reign of Augustus II the Strong that new foreign contingent regulations, based on Saxon ideas, were introduced.